To verify the student's solution, let's start from the original equation and go through the steps to see if the solution is correct.
The equation given is:
\[ \frac{3}{5}t + 7 = -8 \]
- First, we will isolate the term containing \( t \). We can do that by subtracting 7 from both sides:
\[ \frac{3}{5}t = -8 - 7 \]
This simplifies to:
\[ \frac{3}{5}t = -15 \]
- Next, to solve for \( t \), we will multiply both sides by the reciprocal of \( \frac{3}{5} \), which is \( \frac{5}{3} \):
\[ t = -15 \cdot \frac{5}{3} \]
Calculating this gives:
\[ t = -\frac{75}{3} \]
\[ t = -25 \]
Now, let's compare the result we found for \( t \) with the solution provided by the student:
The student found \( t = -9 \), but our calculation shows \( t = -25 \).
Based on this analysis, the correct statement is:
The solution is wrong, because the -9 should be -25.